Analysis of Corner Kick Success in Laliga Santander 2019/2020 - Mitrotasios, M.; Casal, C.; Armatas, V.; Losada, J.; Maneiro, R. (European Journal of Human Movement, 2021)
It is well documented that set pieces represent 30% to 40% of goals scored in elite football, however most studies on set pieces have focused on the analysis of special competitions (World Cup, Euro etc). Thus , the purpose of this study was to examine the effectivene ss of corner kick strategies used in LaLiga Santander during the 2019/2020 season, to identify the Key Performance Indicators (KPI) associated with the outcome of corners kicks and to develop a successful execution model. In total, 3,620 corner kicks execu ted in 380 matches were re corded by the observational methodology and examined through univariate (analysis of proportions), bivariate (Chi - square test for independence X² and ROC area) and multivariate analysis (logistic regression). Results showed that 105 goals (2.9%) were scored from corner kicks. The following KPI were associated with outcome of corner kicks: final result ( X² = 10.644, p = 0.002), time ( X² = 10.422, p < 0.005), number of intervening attackers ( X² = 24.863, p < 0.001), final attempt zone ( X² = 203.13, p < 0.001), number of passes and second play ( X² = 26. 071, p < 0.001). The most effective execution model consisted of a direct delivery, shooting to goal from the front zone or second post. The results present ed here enhance coaches ? understanding on factors that affect corner kicks performance and the most efficient mode of execution.